Observations on the boletes of the Cooloola Sand-mass, Queensland and notes on their distribution in Australia: Part 3. Lamellate taxa - Watling, Roy; Gregory, Norma M. (Edinburgh Journal of Botany, 2010)
The lamellate boletes found in the Cooloola Sand-mass, Queensland are described and discussed in the light of earlier Australian records of paxilloid fungi. Nine species of Paxillus are discussed, two in Tapinella, which is maintained as a separate entity, and 11 are assigned to Phylloporus. Of the last, eight are new records to Australia and two are new species. Three appendices cover various aspects of studies on Australian boletes which have come to light since the publication of this series, including notes on the host-range of the parasitic hyphomycete Sepedonium.